(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background : Recommendations for age at orchidopexy for Undescended Testis (UDT) have changed from time to time in accordance with change of knowledge regarding its pathology and prognostic features. In most developed countries, recommendation for ideal time of orchidopexy is between six months to one year. This study investigates the age of patients who underwent orchidopexy for undescended testis in this institute to assess the current trend of age at orchidopexy in this region. Materials and methods : This is a retrospective study carried out in the Department of Pediatric Surgery, Chittagong Medical College Hospital from January 2017 to December 2019. Patients of UDT who visited the outpatient department, admitted in this ward or underwent orchidopexy in this department were retrospectively evaluated from hospital records, operating theatre register, patient files and admission profile and departmental audits. Number of patients, side of involvement and age distribution were calculated. Results: A total of 218 patients of UDT attended OPD (1.91% of total OPD) 96 patients were admitted (1.33 % of all admissions) and 82 patients underwent orchidopexy (1.48 % of total surgeries) during the study period. Age at orchidopexy ranged from 8 months to 12 years with a median age of 5 year 11 months. Only 5 patients (6.10 %) underwent orchidopexy at the recommended time of between 6 months to one year. Conclusion: Many patients attended OPD after the recommended age and many underwent surgery at a later age which increases their risk of malignancy and testicular atrophy. JCMCTA 2019 ; 30 (2) : 47-51